A study of lovastatin and l-arginine co-loaded PLGA nanomedicine for enhancing nitric oxide production and eNOS expression. Issue 4 (7th January 2022) - Wijaya, Andy; Wang, Yi; Tang, Dan; Zhong, Yuan; Liu, Boyan; Yan, Meng; Jiu, Quhui; Wu, Wei; Wang, Guixue
Abstract : LA and LV were co-loaded in PLGA NPs. PLGA-LA/LV NPs can suppress the proliferation of VSMCs, enhance eNOS mRNA and protein expression in HUVECs, promote SR-B1 mRNA expression, and lower the total cholesterol of blood plasma in C57BL/6 mice. Abstract : Nitric oxide (NO) is an exceptional endogenous biological gas that mediates and regulates physiological and pathological processes in the human body. However, its synthesis process is impaired during athero-progression and formation. Hence, a strategy to boost NO production and target endothelial nitric oxide synthase (eNOS) is crucial and intriguing in atherosclerosis (AS) management. Herein, we prepare l -arginine (LA) and lovastatin (LV) co-loaded PLGA nanomedicine to achieve sustainable release for enhancing NO production. The utilization of LA reveals that LA has dual contributions, acting as a NO donor and enhancing the solubility of LV by stabilizing PLGA NPs. PLGA-LA/LV demonstrated its potential to boost NO in vitro and in vivo confirmed using DAF-FM DA, augment eNOS and p-eNOS mRNA and protein levels, and suppress the ki67 proliferation marker in VSMCs; in addition, it lowers the total cholesterol level of blood plasma in C57BL/6 mice. Moreover, PLGA can protect the compound delivered and enhance the bioavailability to reach and get released in the blood circulation after oral administration. Collectively, our results endow a safe and efficient nanomedicine outcome, specifically with potential for AS management.